2010
DOI: 10.21273/hortsci.45.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Benzyladenine and Gibberellic Acid Application Prevents Abscisic Acid-induced Leaf Chlorosis in Pansy and Viola

Abstract: Drought stress during the shipping and retailing of floriculture crops can reduce postproduction shelf life and marketability. The plant hormone abscisic acid (ABA) mediates drought stress responses by closing stomata and reducing water loss. Applications of exogenous s-ABA effectively reduce water loss and allow a variety of species to survive temporary periods of drought stress. Unfortunately, s-ABA application can also lead to leaf chlorosis, which reduces the overall quality of economically important beddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…In fact, Jiang and Zhang (2001) reported that ABA is a promoter of the antioxidant defense system when plants are under oxidative stress, but high ABA concentration (1000 mgÁL -1 ) induced an excessive production of active oxygen species, which led to an oxidative damage to leaves of maize seedlings. Waterland et al (2010) demonstrated that application of S-ABA in bedding plants induced phytotoxicity. It was also suspected that phytotoxicity was associated with the low pH of ABA solutions, which varied from pH = 2.8 for 3200 mgÁL -1 to pH = 3.8 for 200 mgÁL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Jiang and Zhang (2001) reported that ABA is a promoter of the antioxidant defense system when plants are under oxidative stress, but high ABA concentration (1000 mgÁL -1 ) induced an excessive production of active oxygen species, which led to an oxidative damage to leaves of maize seedlings. Waterland et al (2010) demonstrated that application of S-ABA in bedding plants induced phytotoxicity. It was also suspected that phytotoxicity was associated with the low pH of ABA solutions, which varied from pH = 2.8 for 3200 mgÁL -1 to pH = 3.8 for 200 mgÁL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Application of benzyl adenine have been shown to have effects on many other physiological and developmental processes, including leaf senescence, leaf chlorosis, increase the vase life, delaying senescence of cut carnation by inhibiting ethylene biosynthesis (Cook et al 1985), nutrient mobilization, apical dominance, the formation and activity of shoot apical meristems, floral development, combating drought stress in plants (Waterland et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, s-ABA caused chlorosis on the margin of leaves in impatiens. Foliar chlorosis and leaf abscission have been frequently mentioned as side effects of ABA application (Agehara and Leskovar, 2012;Astacio and van Iersel, 2011;Kim and van Iersel, 2011;Waterland et al, 2010aWaterland et al, , 2010cWeaver and van Iersel, 2014). Chlorosis has been known to accelerate with increasing ABA concentration (Agehara and Leskovar, 2012;Astacio and van Iersel, 2011;Weaver and van Iersel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Plants were held in the greenhouse under the previously described environmental conditions for subsequent evaluations. Half of plants treated with each antitranspirant had water withheld (waterstressed) until all treated plants reached a visual wilt status rating of 3 or below (unmarketable) as described by Waterland et al (2010c). Wilt status ratings were from 1 to 5 with 5 = completely turgid, 4 = soft to the touch but still upright, 3 = starting to wilt, 2 = severely wilted, and 1 = wilted to the point that leaves are dried and desiccated (Waterland et al, 2010a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation